2011
DOI: 10.1098/rsta.2011.0173
|View full text |Cite
|
Sign up to set email alerts
|

Local investigation of the optical properties of subwavelength rectangular holes with a focused beam of electrons

Abstract: The optical properties of rectangular subwavelength holes in a gold film are investigated using the light generated when a focused beam of electrons impinges on the sample close to the hole. Using this technique, multi-spectral maps of the holes are obtained with a resolution beyond the optical diffraction limit. The results show the influence of hole shape on the spectrum of locally scattered light. Rectangular holes of varying shape and size are investigated, and the spatial distribution of the polarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The cathodoluminescence measurements performed by Prangsma et al 27 can be treated similar to our dimensionless scaling parameter approach and lead to L/d of 1.09, 0.87, and 0.75. Following our line of argumentation, for this range of the dimensionless scaling parameter, both modes should be present although the antisymmetric lower-energy mode would be only weakly excited.…”
Section: Acs Photonicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cathodoluminescence measurements performed by Prangsma et al 27 can be treated similar to our dimensionless scaling parameter approach and lead to L/d of 1.09, 0.87, and 0.75. Following our line of argumentation, for this range of the dimensionless scaling parameter, both modes should be present although the antisymmetric lower-energy mode would be only weakly excited.…”
Section: Acs Photonicsmentioning
confidence: 99%
“…Via STEM EELS, Carmeli et al 26 demonstrated the excitation of SPPs up to several 100 nm away from the metal wall of a single rectangular slit in a 200 nm thin Au film and showed the hybridization of SPPs with cavity modes. Prangsma et al 27 performed cathodoluminescence measurements in single slits and arrays of subwavelength slits in a scanning electron microscope. They investigated single slits and three-slit arrays of 100 nm x 260 nm size with varying interslit distances of 240, 300, and 350 nm.…”
mentioning
confidence: 99%
“…It has been demonstrated that by using scanning near-field microscopy , and scanning tunneling microscopy, fundamental scattering properties can be measured. Alternatively, experimental techniques that employ a fast electron beam as excitation source, like electron energy-loss spectroscopy (EELS) and cathodo­luminescence (CL) spectroscopy, have been used to reveal the resonant properties of circular holes, rectangular holes, nanoslits, , and inverse split rings . In this article, we aim to further elucidate the local optical response of individual deep-subwavelength plasmonic holes, by using angle-resolved CL imaging spectroscopy (ARCIS).…”
mentioning
confidence: 99%
“…They exploit the deformable nature of polymers when used as substrates for metamaterials, with an emphasis on looking at how mechanical deformation limits elastic tunability. Meanwhile, Prangsma et al [3] look at how electrons may be used to uncover the optical properties of metamaterial structures. Most work in this area exploits light (photons) for such characterization work, but electrons have been very successfully used in plasmonics, and Prangsma et al [3] continue and extend that work; it may prove a powerful way to explore local effects and local defects in metamaterial structures.…”
Section: Metallic Metamaterials and Plasmonicsmentioning
confidence: 99%